FUNDING SOURCES AND FINANCIAL SUSTAINABILITY OF SMALL-SCALE ENTERPRISES (SSES) IN UGANDA A DESCRIPTIVE CASE STUDY OF KYENGERA TRADING CENTRE-WAKISO DISTRICT - Ssemudu Julius Kamara (Student's Journal of Health Research, 2023)
Background The study analyzed the relationship between funding sources and the financial sustainability of small-scale enterprises the objective of the study was to establish the effect of equity financing on the financial sustainability of Small-scale Enterprises. Methodology The study adopted both descriptive and survey research designs using a population of 160 and a sample size of 140 respondents and the findings were summarized below; Results. There was a weak positive relationship between equity financing and the financial sustainability of SS's within the Kyengera trading center. The (adjusted R-squared) coefficient of determination value of about 0.242 indicates that 24.2% is the variation in the financial sustainability of SSEs.  Conclusion The study concluded Building on the results, it is concluded that improving the financing options would lead to the sustainable growth of small businesses in Uganda. Therefore, the optimal financing model for financing small-scale businesses to enhance their sustainable growth is the integration of the four funding sources comprising traditional debt finance, asset-based financing, crowdfunding, and equity finance. Recommendations Specifically, policymakers such as the government should conduct awareness campaigns through seminars and conferences for small business owners to understand the advantages of these financing options which will in turn enable small businesses to access them and obtain the required funding.